The effect of gold and silver nanoparticles, chitosan and their combinations on bacterial biofilms of food-borne pathogens. Issue 2 (7th February 2020) - Chlumsky, Ondrej; Purkrtova, Sabina; Michova (Turonova), Hana; Svarcova (Fuchsova), Viviana; Slepicka, Petr; Fajstavr, Dominik; Ulbrich, Pavel; Demnerova, Katerina
Abstract: The antimicrobial activity of gold and silver nanoparticles (AuNPs, AgNPs), chitosan (CS) and their combinations was established by determining the minimum inhibitory concentration for planktonic (MICPC80 ) and biofilm growth (MICBC80 ), for biofilm formation (MICBF80 ), metabolic activity (MICBM80 ) and reduction (MICBR80 ), and for the metabolic activity of preformed biofilm (MICMPB80 ). Biofilms were quantified in microtitre plates by crystal violet staining and metabolic activity was evaluated by the MTT assay. Chitosan effectively suppressed biofilm formation (0.31–5 mg ml −1 ) in all the tested strains, except Salmonella enterica Infantis (0.16–2.5 mg ml −1 ) where CS and its combination with AgNPs induced biofilm formation. Nanoparticles inhibited biofilm growth only when the highest concentrations were used. Even though AuNPs, AgNPs and CS were not able to remove biofilm mass, they reduced its metabolic activity by at least 80%. The combinations of nanoparticles with CS did not show any significant positive synergistic effect on the tested target properties.